Business Process Re-Engineering of Direct Cash Drug Inventory at Private General Hospital X, Bandung City - Azka Yasfa Uga; Vicky Dzaky Cahaya Putra (Amkop Management Accounting Review (AMAR), 2026)
One of the main components of the health services is the provision of medications. Although the drug procurement procedure at RSU X Bandung is well implemented, certain obstacles remain, such as lengthy and time-consuming processes. This study aims to comprehensively redesign the drug procurement procedure at RSU X Bandung using the BPR method to enhance efficiency. The research was conducted through several stages of BPR implementation. Throughput efficiency was measured using ASME standards in the direct cash drug procurement process. The initial results indicated an efficiency rate of 68,96%. After process improvements and the elimination of non-value-added activities, efficiency rose to 90,50%, demonstrating a significant improvement in both the effectiveness and the speed of the procurement process.